Cutting Out the Gaps Between Proteases and Programmed Cell Death - Balakireva, Anastasia V.; Zamyatnin, Andrey A. (Frontiers in Plant Science, 2019)
To date, many animal models for programmed cell death (PCD) have been extensively characterized and classified while such efforts in plant types of PCD still remain poorly understood. However, despite a wide range of functional differences between PCD types in animals and plants, it is certain that all of them are regulated through the recruitment of proteases. Most importantly, proteases are able to perform proteolysis that results in a gain or loss of protein function. This principle relies on the presence of proteolytic cascades where proteases are activated upon various upstream stimuli and which lead to repetitive cell death. While protease activation, proteolytic cascades and targeted substrates are described in detail mainly for nematode, human, and mice models of apoptosis, for plants, only fragmentary knowledge of protease involvement in PCD exists. However, recently, data on the regulation of general plant PCD and protease involvement have emerged which deepens our understanding of the molecular mechanisms responsible for PCD in plants. With this in mind, this article highlights major aspects of protease involvement in the execution of PCD in both animals and plants, addresses obstacles and advances in the field and proposes recommendations for further research of plant PCD.